Spatio-temporal analysis of Dengue distribution pattern in Kuantan from 2015-2019 / Mohamad Hizham Mohamad Hanapi and Farah Ayuni Shafie - Mohamad Hanapi, Mohamad Hizham; Shafie, Farah Ayuni (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Dengue fever is a health issue that has been a source of concern throughout Malaysia, notably Healthscope 2021, Vol 4(1): 31-37 Kuantan, Pahang. Dengue fever cases have been recorded on a regular basis in the local community in recent years. This study aimed to examine the spatio-temporal pattern based on yearly dengue surveillance data for five years from 2015 to 2019. To better understand the pattern of dengue cases, a descriptive analysis that included extensive observation of dengue data as well as the distribution of rainfall in Kuantan was carried out in this study. Data on dengue case distributions over a five-year period were gathered from the Ministry of Health “eDengue” system. A total of 6560 dengue cases in Kuantan was used in this study. Spatio-temporal analysis was performed by plotting the dengue cases distribution using the Geographic Information System (GIS) software and applied with the Kernel Density analysis to trace locality patterns in dengue hotspot. The GIS analysis shows centralized hotspot pattern of dengue cases which mostly focus on the sub-district of Kuala Kuantan. Then, the dengue cases distribution pattern was analysed against the rainfall distribution. The statistical analysis by using the Pearson correlation was used to find the relationship between dengue cases and rainfall. The Pearson correlation brought the value of the R² linear (R² = 0.003) which is far from the accepted value by the research community (R² = 0.19). The Pearson correlation value (r = 0.053) was not close enough to the significance value (r = 1). The relationship between dengue and rainfall in Kuantan from 2015 till 2019 was not statistically significant (p>0.05). These findings show a clear spatio-temporal trend of dengue cases in Kuantan and no significant correlation between dengue cases and rainfall pattern, thus providing evidence in directing future field works to probe on factors such as vector abundance and dispersion in the area.